The impact of EFD on vat collection in Tanzania: A case of Morogoro Municipal - Mlima, Wiston J. (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirement for the award of the Degree of Master of Science in Accounting and Finance of Mzumbe University